Transverse blast loading of hollow beams with square cross-sections - Karagiozova, D. (2013)
A model of deformation of a metal hollow section beam under a uniform blast loading is developed in order to reveal the characteristic features of deformation and energy absorption of hollow section beams under such loading. It is established that as a typical structural component a hollow section distinguishes itself from its solid counterpart with two characteristic features of the response. First, a considerably larger kinetic energy is generated in the hollow section beam as the impulsive load is imparted on the upper flange of the beam having a significantly lower mass than the member. Second, a considerable proportion of the blast energy can be absorbed by the local collapse of the section. A two-phase analytical model is proposed. In the first phase, the local collapse of the thin-walled cross-section is determined by using an upper bound approach; and in the subsequent second phase, the global bending of the beam with the distorted section is analyzed by taking into account the effect of axial force. It is demonstrated that mass distribution in the hollow section is an important factor in determining the energy partitioning between the local deformation phase and global bending of the hollow beam. Reasonable agreement is obtained with the experimental data published in the literature [Jama HH, Nurick GN, Bambach MR, Grzebieta RH, Zhao XL, Steel square hollow sections subjected to transverse blast loads, Thin-Walled Structures 2012;53:109–122].